معيار اختصاصِ القضاء العسكري في الشأن العسكري - الشلبي, علاء الدين; الريماوي, عبد الملك (University of Eloued جامعة الوادي, 2021)
تنصب هذه الدراسة على الولاية القضائية للقضاء العسكري الفلسطيني من حيث بيان معيار تحديد الاختصاص للقضاء العسكري القائم على معيار الاختصاص الشخصي او معيار الاختصاص الموضوعي، حيث تبنى المشرع الفلسطيني أكثر من معيار في تحديد إختصاص القضاء، فقد أخضع لأحكامه بصفة شخصية مجموعة محددة لاختصاص القضاء العسكري، وبصفة موضوعية، كذلك حاولت الدراسة الوقوف على اختلافات التشريعات المنظمة للقضاء العسكري في العديد من الدول، ومقارنتها بالتشريعات الوطنية في فلسطين. This study focuses on the jurisdiction of the Palestinian military judiciary in terms of clarifying the criterion for determining the jurisdiction of the military judiciary based on the criterion of personal jurisdiction or the criterion of objective jurisdiction, as the Palestinian legislator has adopted more than one criterion in determining the jurisdiction of the judiciary. In an objective manner as well.The study attempted to identify the differences in legislation regulating the military judiciary in many countries, and to compare it with the national legislation in Palestine.
The jurisdiction of the military judiciary in military matters
مقال
Keywords: القضاء العسكري، المعيار الموضوعي، المعيار الشخصي، التشريعات العسكرية.; military justice, objective standard, personal standard, military legislation.